A mixed-methods sequential explanatory design comparison between COVID-19 infection control guidelines’ applicability and their protective value as perceived by Israeli healthcare workers, and healthcare executives’ response - Gesser-Edelsburg, Anat (Antimicrob Resist Infect Control, 2020)
BACKGROUND: Healthcare workers (HCWs) are on the front line of the COVID-19 outbreak, and their constant exposure to infected patients and contaminated surfaces puts them at risk of acquiring and transmitting the infection. Therefore, they must employ protective measures. In practice, HCWs in Israel were not fully prepared for this sudden COVID-19 outbreak. This research aimed to identify and compare: (1) Israeli HCWs’ perceptions regarding the official COVID-19 guidelines’ applicability and their protective value, and (2) HCWs executives’ response to HWCs’ concern regarding personal protective equipment (PPE) shortage. METHODS: A mixed-methods sequential explanatory design consists of: (1) An online survey of 242 HCWs about the application of the guidelines and PPE, and (2) Personal interviews of 15 HCWs executives regarding PPE shortage and the measures they are taking to address it. RESULTS: A significant difference between the perceived applicability and protective value was found for most of the guidelines. Some of the guidelines were perceived as more applicable than protective (hand hygiene, signage at entrance, alcohol rub sanitizers at entrance, and mask for contact with symptomatic patients). Other were perceived as less applicable than protective (prohibited gathering of over 10 people, maintaining a distance of 2 m’, and remote services). CONCLUSIONS: HCWs need the support of the healthcare authorities not only to provide missing equipment, but also to communicate the risk to them. Conveying the information with full transparency, while addressing the uncertainty element and engaging the HCWs in evaluating the guidelines, are critical for establishing trust.